2023
DOI: 10.3390/nu15030671
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dietary Calcium and Age-Related Macular Degeneration

Abstract: Background: Mineral element supplements are widely used in the older adult population. However, little is known of their impact on the progression of age-related macular degeneration (ARMD). The aim of this study was to examine the association between dietary micronutrients and ARMD in older adults. Methods: We enrolled 5227 participants from the National Health and Nutrition Examination Survey (NHANES 2005–2008) in this cross-sectional study. ARMD was evaluated using an ophthalmic digital imaging system and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…It is also related to retinal vascular diameter and length, which are important in patients with age-related macular degeneration, as this decreases and narrows during the course of the disease [ 416 , 417 ]. Additionally, it has been reported that some eye diseases, such as glaucoma and macular degeneration, are related to the alteration of calcium-dependent mechanisms, because a high concentration of calcium was an important factor inducing fibrosis, which contributed to fibrotic damage in glaucomatous optic neuropathy [ 418 ]. Therefore, it is reasonable to assume that dietary calcium could play an important role in the progression of age-related macular degeneration [ 418 ].…”
Section: The Importance Of Dietary Patterns On Visual Healthmentioning
confidence: 99%
“…It is also related to retinal vascular diameter and length, which are important in patients with age-related macular degeneration, as this decreases and narrows during the course of the disease [ 416 , 417 ]. Additionally, it has been reported that some eye diseases, such as glaucoma and macular degeneration, are related to the alteration of calcium-dependent mechanisms, because a high concentration of calcium was an important factor inducing fibrosis, which contributed to fibrotic damage in glaucomatous optic neuropathy [ 418 ]. Therefore, it is reasonable to assume that dietary calcium could play an important role in the progression of age-related macular degeneration [ 418 ].…”
Section: The Importance Of Dietary Patterns On Visual Healthmentioning
confidence: 99%
“…8 Previous studies on GERD have discussed some prevalence and risk factors globally and locally. 2,4,5,[9][10][11] However, the studies lack some profiles on the inpatients and outpatients of clinically diagnosed GERD patients, particularly in West Sumatra. Therefore, this study aimed to describe the characteristics of GERD patients in Dr. M. Djamil Padang Central General Hospital as the tertiary referral hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, an ever-growing cadre of researchers has begun to discern the nexus between diet and ocular physiology and pathology. Prior investigations have underscored the a rmative impact of nutrient intake, including lutein, proteins, and carotenoids, on ocular maladies such as diabetic retinopathy, age-related macular degeneration, and retinopathy of prematurity [14,15]. Simultaneously, an injudicious dietary regimen is also deemed a pivotal precipitant of several ocular ailments.…”
Section: Introductionmentioning
confidence: 99%